The Effect of Foliar Application of Zinc and Iron at Different Developmental Phases on the Quantitative and Qualitative Characteristics of Two Cultivars of Dryland Wheat (Triticum aestivum L.) - Sh Ajam; A Biabani; R Mohammadi; A Rahemi Karizaki; H Ghorbani Vaghei (پژوهشهای زراعی ایران)
IntroductionWheat (Triticum aestivum L.) is a widely cultivated crop across diverse soil types, and enhancing its yield, both quantitatively and qualitatively per unit area is a key agricultural priority in the country. Micro elements play a key role in improving the quality performance of products and even human health. Foliar spraying in arid and semi-arid areas, which affects the osmotic pressure of absorption and activity of these elements, is of special importance. t is essential to develop high-yielding cultivars with enhanced micronutrient uptake efficiency and strong tolerance to various stresses. Recently, Aseman and Paya dryland wheat cultivars have replaced other cultivars in Golestan province due to their higher yield, but there is no specific information about the agricultural characteristics of these cultivars, including their reaction to zinc and iron micronutrient fertilizers in the grain. Therefore, this study investigated the effects of zinc and iron fertilization, along with optimal foliar application timing, on the quantitative and qualitative traits of Aseman and Paya wheat cultivars under the climatic conditions of Gonbadkavous.Materials and MethodsThis study was conducted as factorial design based on randomized complete block design (RCBD) with three replications. The first factor was the foliar application of micronutrients at three levels (no micronutrient application or pure water, foliar application of 4‰ zinc chelate, and 6‰ iron chelate) and the second factor was the timing of foliar applications at three levels (application at the tillering stage, stem elongation stage, and grain filling stage). The third factor consisted of wheat cultivars (Aseman and Paya). In total therefor 18 treatments were applied in each replication. Chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids were measured using the Arnon method one week after the implementation of all treatments. The Kjeldahl method was used to measure the protein content of the grain, and grain yield, grain concentrations of iron and zinc, and harvest index were calculated.Results and DiscussionThe results showed that the two cultivars Aseman and Paya had significant differences in grain yield and harvest index, number of spikelets, and the amount of chlorophyll and carotenoids. The foliar treatment (iron, zinc and no foliar application) caused a significant increase in the concentration of iron and zinc in the grain compared to the control, but it did not affect the grain performance, harvest index, grain protein percentage and chlorophyll pigments. The interaction effect of cultivar treatments foliar spraying time showed that the highest value of grain performance was obtained with the application of micronutrient elements in the stemming stage of the Paya cultivar with an average of 730 kg ha-1. Basically, wheat nutrition in drylands is more complicated than in irrigated lands. Because in such conditions, the management of nutrients should be adjusted based on the expected moisture regime in the region.The amount of production in drylands is primarily influenced by weather conditions, especially rainfall, that is, in the conditions of applying proper agricultural management and choosing the right variety for the region, the optimal production will depend on the existence of favorable environmental conditions, as well as the cultivars adapted to the lands and regions.ConclusionFoliar application of zinc and iron, as a management strategy to improve the nutritional status of wheat under dry conditions, significantly increased the concentration of zinc and iron in the grain by 55% and 100%, respectively. However, under the prevailing drought conditions of the study area, this treatment did not result in a significant increase in grain yield, harvest index, or grain protein content. This shows that other factors such as water stress, inappropriate crop management and genetic characteristics of the variety play a more decisive role in wheat yield. Choosing the right cultivar that is compatible with environmental conditions is one of the factors that can help improve wheat yield. In this research, Paya variety with an average yield of 675 kg ha-1 showed better performance than Aseman variety with an average yield of 616 kg ha-1. Also, the effect of variety x time of foliar spraying also had an effect on the yield and the best yield was observed in Paya cultivar with foliar spraying at the stemming stage with an average yield of 729 kg ha-1. This agricultural method can be used as a short-term solution to reduce nutritional problems caused by the lack of these elements and improve food security indicators.AcknowledgmentThe cooperation of the Honorable Research Assistant of the Faculty of Agriculture of Gonbadkavos University in order to secure the credit of the project and the Honorable Head of the Gonbadkavos Agricultural Research Station for providing the grain s of the studied cultivars and the necessary cooperation are sincerely appreciated.